A case of chronic mesenteric ischemia managed by ascending aorta to superior mesenteric and hepatic artery bypass - Nambiar, Harilal V.; Manappallil, Robin George; Aikot, Sylesh; V., Pramod (International Surgery Journal, 2017)
Chronic mesenteric ischemia is a rare and life-threatening condition which occurs due to occlusion of two or more mesenteric arteries following atherosclerosis. Multi-vessel revascularization forms the mainstay of treatment. This is a case of a middle-aged smoker who presented with abdominal angina and was diagnosed to have chronic mesenteric ischemia due to atherosclerotic occlusive aortic disease with coeliac artery and superior mesenteric artery occlusion. He was successfully managed with extra anatomic bypass from the ascending aorta to superior mesenteric and hepatic artery.